Assessment of disorders in childhood and adolescence - Youngstrom, Eric Arden; Prinstein, Mitchell J., 1970-; Mash, Eric J.; Barkley, Russell A., 1949- (New York The Guilford press, 2020)
"Now in an its fifth edition, this leading text and clinical guide offers best-practice recommendations for assessing a comprehensive array of child and adolescent mental health problems and health risks. Leading authorities provide an overview of each disorder and describe methods and procedures that take into account the developmental, biological, familial, and cultural contexts of children's problems and that can inform sound clinical decision making. The fifth edition has been thoroughly updated with the growing knowledge base on child and family disorders and evidence-based assessment"--
Revised edition of: Assessment of childhood disorders / edited by Eric J. Mash, Russell A. Barkley. 4th ed. c2007.
Includes bibliographical references and index.
Keywords: Child psychopathology -- Diagnosis; Adolescent psychopathology -- Diagnosis; Psychodiagnostics